Gestión económica e impuesto a la renta - Medrano Cornejo, Humberto (2021)
Congress delegated the power to legislate on economic management and competitiveness to the Executive Branch, specifically, said authorization covered tax matters and, within this, rules relating to the deduction of expenses in portfolio income, so that the aforementioned are not improperly used to generate tax shields or finance personal requirements. Likewise, the indirect share transfer regime could be modified and a legal definition of the concept of “accrual” could be incorporated, in order to have a specific legal regulation that avoids the inaccuracies that usually occur from other perspectives. This article analyzes the scope of the changes introduced, in respect to the aforementioned extremes.